Design and development of optimal route planning software for the inspection of earthquake monitoring stations - Weifeng Zhang; Jie Pan; Dong Fan; Liangliang Sun; Guibao Zhao; Jingsheng Li (地震科学进展)
With the increasing importance of earthquake monitoring work, the planning of inspection routes plays a key role in improving the efficiency of inspection work and ensuring the accurate and continuous observation data. This article introduces the importance of inspection of earthquake monitoring stations and the limitations of existing inspection methods, and discusses the design and development of optimal route planning software for inspection of earthquake monitoring stations. The article expounds the design concept, main functions and technical implementation of the software, describes the design of key modules in detail, points out the issues that should be paid special attention to optimize the inspection route, and looks forward to the future application prospect of the software. The successful development and application of this software will provide strong technical support for the inspection work of earthquake monitoring stations, and also provide a useful reference for inspection route planning in other fields.